Decreased serum glicentin concentration in patients with severe and morbid obesity. (March 2018) - Raffort, Juliette; Panaïa-Ferrari, Patricia; Lareyre, Fabien; Blois, Mathilde; Bayer, Pascale; Staccini, Pascal; Fénichel, Patrick; Chinetti, Giulia
Background: Proglucagon-derived hormones represent a family of peptides mainly produced in the pancreas and the intestine. While several proglucagon-derived peptides play key roles in metabolic diseases, little is known about glicentin. The aim of the present study was to investigate serum glicentin concentrations in individuals with adult obesity and to study its potential link with various metabolic parameters. Methods: Fifty-two individuals with normal body mass index (BMI < 25 kg/m 2 ) and 39 patients with severe or morbid obesity (BMI > 35 kg/m 2 ) were prospectively included at the University Hospital of Nice between January 2014 and April 2016. Clinical data were recorded, and a fasting blood sample was collected to measure glicentin, glucose, insulin, C-peptide, total cholesterol, triglyceride, LDL and HDL-cholesterol. In addition, a homeostasis model assessment for insulin resistance (HOMA2-IR) was also calculated. Results: Patients with severe and morbid obesity had significantly higher plasma glucose, together with higher serum concentrations of insulin, C-peptide, HOMA2-IR, triglyceride, LDL-cholesterol and lower serum concentrations of HDL-cholesterol compared with individuals with a normal body mass index. The obese patients displayed significantly lower fasting serum concentrations of glicentin compared with subjects with a normal body mass index (12 pmol/L vs. 24 pmol/L, P  < 0.0001). In the total population, fasting glicentin concentrations did not correlate with BMI, glycaemic parameters (glucose, insulin, C-peptide, HOMA-IR) or lipid parameters (total cholesterol, triglyceride, LDL and HDL-cholesterol). Conclusion: To the best of our knowledge, this is the first study reporting serum glicentin concentrations in healthy lean and obese adult subjects. We found that fasting serum glicentin concentrations are decreased in patients with severe or morbid obesity suggesting the potential interest of this peptide in obesity and metabolic-related disorders.